A numerical rotating water tank can reproduce the Coriolis effect on the urban heat dome flow. (1st February 2023) - Fan, Yifan; Zhang, Yan; Wang, Shaopeng; Wang, Xiaoxue; Lu, Jiang; Ge, Jian
Abstract: Urban heat dome flow forms under calm background conditions, which has large impacts on urban ventilation, building energy consumption and pollutants dispersion. With ongoing rapid and intense urbanisation, an increasing number of megacities have emerged. The hydraulic diameter of megacities can reach beyond than 20 km, leading to the Coriolis force playing an important role in urban heat dome flow over high-latitude cities. In this study, based on the Rossby number similarity criterion, a numerical rotating tank model (length scale of 0.5 m) was designed and compared with the real atmospheric scale (length scale of 20 km) large eddy simulation (LES) models. The reduced-scale model reproduced the deflection behaviour of the urban heat dome flow compared with those of the atmospheric cases at the same Ro number. To quantify the magnitude of deflection, an outflow angle γ in the upper-level divergent outflow region was defined. The outflow angle of the reduced-scale cases agrees well with those of the corresponding atmospheric cases. The velocity fields, temperature fields, vorticity fields, and dome structures were also analysed in both reduced scale numerical reduced-scale cases and real atmospheric scale cases. The computational time in reduced-scale cases can be reduced significantly with acceptable accuracy. These findings suggest that a rotating tank can be used to study the effect of the Coriolis force. Highlights: The Coriolis force on buoyancy-driven urban heat dome is modeled and validated. Based on the Ro similarity theory, a numerical rotating tank is set. The rotating tank model reproduces the deflection behaviour of the dome flow. Deflection effects on city-scale airflow and heat transport are understood. The model enables future studies coupling of heat field, cooling demand and energy resilience.